Brazilian Foreign Policy and Trade Balance: a brief analysis of the Jânio Quadros/João Goulart and Castelo Branco governments (1961 – 1967) (Management & Public Policies Journal, 2022)
This paper presents a brief analysis of the Brazilian Foreign Policy (PEB) and the relationship with the results of the trade balance during the governmental periods of Jânio Quadros (1961), João Goulart (1961-1964) and Castelo Branco (1964-1967), by from the perspective of trade relations between Brazil and the United States. For this, from a methodological point of view, the research, of an exploratory-descriptive character, examined the conduction of Brazilian foreign policy during the early 1960s - especially the official alignment of the Itamaraty - and, on the other hand, collected the data of the former Ministry of Development, Industry and Foreign Trade (MDIC), now absorbed by the Ministry of Economy of the Brazilian Federal Government, to examine the indicators and results of the Brazilian trade balance, especially its relationship with the USA. The research results in the conclusion that Brazilian foreign policy actions, even after the 1964 military coup, did not significantly impact the results of the trade balance of the period in question, where other elements and long-term approaches must be considered for the interpretation of current trade and its link with the performance of the foreign policy of the States.